کاریگەری موزیک لەسەر لایەنی دەروونی مرۆڤ - ڕشید, بەختیار حسین (Sulaimani Journal for Humanities, 2023)
This research will shed light on the impact of music on human psyche and discusses all the approaches that have been done in this area of the study. In any society, music as an art has been used in many different areas and each of these areas has its own important in society. Moreover, many scholars through their researches, books, and practical approaches reveal the importance of music. This research is a theoretical attempt to explain an important subject which is up to the moment unknown to Kurdish society. Music Therapy is the main heading that this research will talk about, and this subject in Canada, US, Australia, and many other European countries familiar and number of researches have been done on that matter. Specialized people in many areas such as Psychology of music, Neuromusicology, Sociology of music, and Aesthetics of music, in many different ways discussed the importance of music on human psyche and their daily activities. Those who are specialized in Music Therapy according to the above professions and based on their crucial finding have done practical researches in mental hospitals, schools, senior housing and many other places and used music as a remedy for those people who have somewhat psychological problems. In addition, in many hospitals, music used as a relaxing and healing factor for those patients who have gone through surgical treatment. This research makes use of many theoretical and practical approaches that deal with human psyche, mind, and behavior and according to their methodical findings this research is born.